Make vs. buy decisions: A process incorporating multi-attribute decision-making - Platts, K.W.; Probert, D.R.; Cáñez, L. (International journal of production economics, 2002)
The need for companies to develop consistent and competitive manufacturing strategies is now well established. A fundamental question in the development of a manufacturing strategy is the determination of what the company will make and what it will buy, i.e. the make vs. buy (MvB) decision. Historically, such decisions were often made primarily on grounds of cost, however, in recent years there has been an increasing recognition of the strategic implications of these decisions and the need to take into account a wide range of factors other than cost. This paper describes the results of an ongoing study to investigate the factors affecting the making of MvB decisions and the creation of a process to guide industrial companies through making such decisions. The process is based on operationalising a framework which addresses technology and manufacturing processes, supply chain management and logistics, support systems, and costs. Companies following the process are taken through a structured sequence involving identification of triggers for the MvB decision, and the comparison of in-house and external sourcing judged against the areas above. Multi-attribute decision-making is used to provide an overall MvB recommendation. The paper describes the MvB process, its application in an industrial case and concludes with a discussion of its contribution to both academic understanding of the subject, and improvement of industrial practice.